From cooking vessels to cultural practices in the late Bronze Age Aegean - Hruby, Julie; Hruby, Julie; Trusty, Debra; Trusty, Debra (Oxbow Books, 2017)
"Late Bronze Age Aegean cooking vessels illuminate prehistoric cultures, foodways, social interactions, and communication systems. While many scholars have focused on the utility of painted fineware vessels for chronological purposes, the contributors to this volume maintain that cooking wares have the potential to answer not only chronological but also economic, political, and social questions when analysed and contrasted with assemblages from different sites or chronological periods. The text is dedicated entirely to prehistoric cooking vessels, compiles evidence from a wide range of Greek sites and incorporates new methodologies and evidence. The contributors utilise a wide variety of analytical approaches and demonstrate the impact that cooking vessels can have on the archaeological interpretation of sites and their inhabitants. These sites include major Late Bronze Age citadels and smaller settlements throughout the Aegean and surrounding Mediterranean area, including Greece, the islands, Crete, Italy, and Cyprus. In particular, contributors highlight socio-economic connections by examining the production methods, fabrics and forms of cooking vessels. Recent improvements in excavation techniques, advances in archaeological sciences, and increasing attention to socioeconomic questions make this is an opportune time to renew conversations about and explore new approaches to cooking vessels and what they can teach us"--Publisher description